Renoprotective effect of chronic treatment with sodium-glucose cotransporter 2 inhibitors and its associated factors in Japanese patients with chronic heart failure and diabetes. (December 2022) - Yokouchi, Go; Horio, Takeshi; Matsumoto, Naoki; Fukuda, Kohei; Yoshimura, Ryutaro; Fujiwara, Ryosuke; Matsuoka, Yujiro; Sakamoto, Yuya; Iwashima, Yoshio; Oshiro, Yoshiyuki; Fujimoto, Kohei; Kasayuki, Noriaki
Abstract: Background: Recent clinical trials have shown that sodium-glucose cotransporter 2 (SGLT2) inhibitors have beneficial effects on renal function in heart failure patients. This study confirmed the renoprotective effect of treatment with SGLT2 inhibitors in Japanese patients with chronic heart failure and diabetes and further investigated what cardiac/hemodynamic and noncardiac factors are involved in its effect. Methods: Eligible 50 outpatients with chronic heart failure and type-2 diabetes mellitus chronically taking SGLT2 inhibitors were enrolled. Annual changing rates of estimated glomerular filtration rate (eGFR) were compered before and after treatment with SGLT2 inhibitors and the associations of the change in eGFR slope after SGLT2 inhibitor administration with changes in various clinical and echocardiographic parameters were evaluated. Results: The mean follow-up periods before and after SGLT2 inhibitor administration were 2.6 and 1.9 years, respectively. Changing rates of eGFR per year were significantly improved after treatment with SGLT2 inhibitors (−5.78 ± 7.67 to −0.43 ± 10.81 mL/min/1.73 m 2 /year, p = 0.006). The daily doses of loop diuretics were not altered after SGLT2 inhibitor administration. Neither decreased body weight nor increased hematocrit was associated with the change in eGFR slope before and after SGLT2 inhibitor administration. While, the decrease in inferior vena cava diameter and the increase in its respiratory collapsibility were significantly correlated with the improvement of eGFR decline slope after SGLT2 inhibitor administration. Conclusions: Our findings indicated that chronic treatment with SGLT2 inhibitors ameliorated annual decline in eGFR in Japanese patients with chronic heart failure, suggesting the possibility that the improvement of venous congestion was involved in its renoprotective effect.